Cuticle structure and chemical composition of waxes in Phaeoceros laevis (L.) Prosk (Notothyladaceae, Anthocerotophyta) - Matos, Tamara Machado; Cruz, Rafael; Peralta, Denilson Fernandes; Melo-de-Pinna, Gladys Flávia de Albuquerque; Santos, Déborah Yara Alves Cursino dos (Frontiers in Plant Science, 2022)
The development of a hydrophobic cuticle covering the epidermis was a crucial evolutionary novelty ensuring the establishment of land plants. However, there is little information about its structure and chemical composition, as well as its functional implications in avascular lineages such as Anthocerotophyta. The main goal of the present study was to compare the gametophyte and sporophyte cuticles of Phaeoceros laevis. Semithin sections were analyzed through light microscopy (LM), cuticle structure was evaluated by transmission electron microscopy (TEM) and epicuticular wax morphology was analyzed by scanning electron microscopy (SEM). Total waxes were analyzed by CG/MS, and the components were identified based on the mass spectra. A thin lipophilic layer was detected on the sporophyte surface, structured as a stratified cuticular layer, similar to the well-known structure described for vascular plants. On the other hand, the gametophyte cuticle was observed only with TEM as a thin osmiophilic layer. SEM analyses showed a film-type wax on the surface of both life phases. The wax layer was eight-fold thicker on the sporophyte (0.8 µg cm-2) than on gametophyte (0.1 µg cm-2). Possible mechanical and/or drought protection are discussed. Fatty acids, primary alcohols, and steroids were identified in both life phases, while the kauren-16-ene diterpene (3%) was detected only on the sporophyte. Although no alkanes were detected in P. laevis, our findings unveil great similarity of the sporophyte cuticle of this hornwort species with the general data described for vascular plants, reinforcing the conservative condition of this character and supporting the previous idea that the biosynthetic machinery involved in the synthesis of wax compounds is conserved since the ancestor of land plants.